Advanced understanding of local wetting behaviour in gas-liquid-solid packed beds using CFD with a volume of fluid (VOF) method. (12th October 2017) - Du, Wei; Zhang, Jianzhou; Lu, Panpan; Xu, Jian; Wei, Weisheng; He, Guangxiang; Zhang, Lifeng
Graphical abstract: Highlights: A new parameter describing local liquid holdup is proposed in this study. Gas-liquid flow hysteresis can be better understood by the statistical analysis. Effects of temperature and pressure conditions on flow behaviour are studied. Abstract: Gas-liquid-solid packed bed reactors or trickle-bed reactors (TBRs) have been widely employed in various industrial applications such as hydrocracking, selective hydrogenation process of gas oil, wastewater treatment and so on. Since the multiphase flow in TBRs is complex, uniform liquid distribution can hardly be obtained. The liquid coverage on particles at various locations in the bed affects the overall reactor performance. In this work, computational fluid dynamics (CFD) simulations with a volume of fluid (VOF) model were employed to investigate liquid mal-distribution at the micro-level in a packed bed reactor. In this study, two different parameters (the local liquid coverage (HL ) and local liquid holdup (hL )) were employed to describe liquid distribution on individual particles. The liquid distribution at different particle layers was investigated. The results revealed that the distributions for local liquid coverage and local liquid holdup were similar. The wetting efficiency and the liquid residence time decreased with increasing the voidage. In a packed bed with cylindrical particles, the capillary effect cannot be ignored in smaller channels formed between the particles, leading to higher flow resistance. It was also found that the wetting efficiency and liquid film thickness increased with an increase in the liquid velocity. Both wetting efficiency and the time required to reach steady state decreased when increasing the contact angle. The flow on particle surface could change from rivulet to film as the liquid density decreased. The newly unveiled information of local liquid holdup distribution could significantly advance the understanding of gas-liquid flow hysteresis inside packed beds, based on which the reactor performance can be further improved.